Integrated Knowledge in Tourism System - Pimonsompong, Chalongsri (JOURNAL OF SOUTHERN TECHNOLOGY, 2024)
The objective of the article was to explore the explanation of tourism extra- disciplinarity in the tourism system framework which begins with two philosophical concepts: ‘Ontology’ and ‘Epistemology’ which are the advent of “Hard Sciences” and “Soft Sciences” and the expansion of several other disciplines. According to the “Tourism and Hotel Discipline Qualifications Framework” announced by Office of Higher Education Commission (OHEC) in 2010, educational institutions have improved their curriculum and better learning management in this field. However, there remain questions about the clear academic nature of tourism discipline that plays a crucial role in the development of demand and supply in tourism system. The findings based on the analysis and synthesis of literature review revealed that tourism is an extra discipline that applied principles, concepts and theories from the fields of science, social sciences, humanities and arts, indigenous knowledge, values-based knowledge, and problem-centered knowledge, which were then synthesized and integrated to align with the context of the studied research area. They were also surveyed and experimented obtain new body of knowledge in the field of tourism that can be used to promote and develop the tourism demand and supply or serve as a model for developing tourism system that is interconnected, which will result in strengthening and modernizing Thailand’s tourism industry.